Teaching the Millennial Generation in the Religious and Theological Studies Classroom - Bauman, Whitney (Teaching theology and religion, 2014)
This essay provides an overview of the distinctive challenges presented to teaching and learning in religious and theological studies by the conditions and characteristics of “millennial” students. While the emerging literature on this generation is far from consistent, it is still instructive and important to engage, as students that are immersed in technology and social networking have different facilities and difficulties that educators would do well to carefully address and critically employ. Teachers in theological and religious studies are distinctly positioned to grapple with such conditions, particularly around the practices of identity formation, media literacy, and embodiment. Attention to the development of such practices engages key issues for both the millennial students and the religious and theological studies teacher: virtual reality, spiritual identity, globalization and violence, critical consumption and ethical creativity, focused and contemplative thinking, and intercultural and interpersonal respect.